Age Specifics of Preschoolers' Role Play in Open Object Environment - Ryabkova I.A; Smirnova E.O; Sheina E.G (Moscow State University of Psychology and Education, 2019)
This paper is devoted to the research of preschoolers' free play in an open object environment.The results of observations showed different dynamics of play activity in different age groups (3, 4, 5 and 6 years).In the two younger groups, role renaming was observed in a third of the sample, and in the majority of children it was accompanied by certain changes in the appearance and by fragmentary play actions.Beyond 5 years the frequency of renaming increased - two-thirds of children called themselves a role name and almost all played roles.Many children created complex plots with a lot of branching.In the oldest group there was a significant decline in renaming and changing of the appearance (less than half of the children) as compared to the 5-year-olds, and almost complete absence of role play actions.This paper lists the roles that modern preschoolers reproduce in their play.The study shows that the role does not precede the play, but is born in the process of various actions, including exploratory and trialing actions, with objects.The importance of exploratory, manipulative activity for the emergence and development of the role is underlined.An open object environment promotes the development of such activity.